2021
DOI: 10.1007/s00394-021-02738-2
|View full text |Cite
|
Sign up to set email alerts
|

Betaine in ameliorating alcohol-induced hepatic steatosis

Abstract: Alcohol-associated liver disease (AALD) is one of most common chronic liver diseases. Hepatic steatosis is the earliest stage in AALD pathological spectrum, reversible by alcohol abstinence. Untreated steatosis can progress to steatohepatitis, fibrosis and/or cirrhosis. Considering the difficulties in achieving complete abstinence, challenges in disease reversal at advanced stages, high costs of AALD management and lack of standardised prescribed medications for treatment, it is essential to explore low-cost n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The pathways relating betaine to fetal growth are unknown. Studies have linked betaine with lipid metabolism [20,21] and altered cord blood lipid concentrations were correlate with birth weight [22,23] , therefore, we speculate that elevated betaine concentrations can lead to lipid metabolism disorders, resulting in an increased risk of SGA. However, we found no signi cant association between cord blood betaine serum levels with lipid levels, suggesting it may be mediated by pathways other than lipid metabolism.…”
Section: Discussionmentioning
confidence: 84%
“…The pathways relating betaine to fetal growth are unknown. Studies have linked betaine with lipid metabolism [20,21] and altered cord blood lipid concentrations were correlate with birth weight [22,23] , therefore, we speculate that elevated betaine concentrations can lead to lipid metabolism disorders, resulting in an increased risk of SGA. However, we found no signi cant association between cord blood betaine serum levels with lipid levels, suggesting it may be mediated by pathways other than lipid metabolism.…”
Section: Discussionmentioning
confidence: 84%
“…The evidence showed that betaine enabled to protect internal organs, improve vascular risk factors, and enhance performance ( 8 ). The positive effects of betaine supplementation in treating hyper-homocystinurics ( 23 , 24 ) and alcohol-induced hepatic steatosis ( 25 ) have also been elucidated. As a multifunctional agent, betaine possesses various physiological activities that include anti-oxidation, anti-inflammation, and anti-fibrosis ( 26 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism to increase lipolysis in adipose tissue after chronic ethanol ingestion is by affecting fibroblast growth factor 21 [ 52 ]. In addition to this, alcohol also alters the adipogenic pathway by upregulating sterol regulatory element-binding proteins (SREBPs) and inactivating peroxisome proliferator-activated receptor-alpha (PPARα) [ 53 ]. White adipose tissue (WAT) releases adipokines such as adiponectin leptin and other adiponectin, and therefore WAT has recently been regarded as a major secretory organ [ 52 ].…”
Section: Pathogenesis Of Aldmentioning
confidence: 99%